Diversity and specificity of orchid mycorrhizal fungi in a leafless epiphytic orchid, Dendrophylax lindenii and the potential role of fungi in shaping its fine-scale distribution - Johnson, Lynnaun J. A. N.; Kane, Michael E.; Zettler, Lawrence W.; Mueller, Gregory M. (Frontiers in Ecology and Evolution, 2023)
Orchids grow in diverse habitats worldwide with most (approximately 69%) growing on trees as epiphytes. Although orchid mycorrhizal fungi have been identified as potential drivers for terrestrial orchid distribution, the influence of these fungi on the fine-scale distribution of epiphytic orchids is poorly understood. In this study, we investigated the mycorrhizal fungal community and fine-scale distribution of Dendrophylax lindenii, a rare and endangered epiphytic orchid that is leafless when mature. We used amplicon sequencing to investigate the composition of orchid mycorrhizal fungi in the roots of 39 D. lindenii individuals in their natural habitat, the swamps of Florida. We compared the orchid mycorrhizal fungi of D. lindenii to those of co-occurring epiphytic orchids, as well as to the orchid mycorrhizal fungal communities of bark from potential host trees, with and without D. lindenii. Our results show that D. lindenii has a high specificity for a single Ceratobasidium species, which is widely distributed on phorophytes and detected in both wet and dry periods in the orchid’s habitat. This Ceratobasidium species was mostly absent or only recorded in low frequency in the roots of co-occurring epiphytic orchids. Phylogenetic analysis documented that this Ceratobasidium was conspecific with the strain that is used to germinate D. lindenii ex-situ. However, our findings suggest that laboratory germinated adult D. lindenii transplanted into the field had lower read abundances of this Ceratobasidium compared to naturally occurring plants. These findings suggest that this orchid mycorrhizal fungus may play a significant role in the fine-scale distribution of naturally occurring D. lindenii.